Identifying the concept of space in paintings with Malay ornament design / Haslinda Abd Razak, Rafeah Legino and Baharim Khusil @ Samuri - Abd Razak, Haslinda; Legino, Rafeah; Khusil @ Samuri, Baharim (Faculty of Art and Design, 2022)
Space provides an essential quality in visual art, as it encompasses the arrangement of basic principles of art with other elements of design that transform the idea into creative aesthetic values. Misinterpreted decorative painting composition as flat space has created a misunderstanding of the depth approach in utilizing motifs and patterns. This study was conducted to examine comprehensively the concept of space that emphasized Malay ornament design as well as techniques and approaches. Twenty-eight decorative paintings from National Art Gallery, Malaysia permanent collections have been selected as sampling. Observation and tracing methods were used to further investigate the types of space that were explored in these paintings. As a result, three types of space were identified and shallow space was frequently present in these decorative paintings. Subsequently, this study will increase the understanding and diminish misjudgment of space with decorative painting composition, especially through the application of Malay ornament design.